2017
DOI: 10.1136/gutjnl-2016-313035
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies HLA-DR variants conferring risk of HBV-related acute-on-chronic liver failure

Abstract: Our genome-wide association study identified as the major locus for susceptibility to HBV-related ACLF. Our findings highlight the importance of HLA class II restricted CD4+ T-cell pathway on the immunopathogenesis of HBV-related ACLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…As reported, CD4 + T‐cell priming is pivotal to activate professional antigen‐presenting cells necessary for the induction of CD8 + T‐cell responses . And a recent genome‐wide association study identified that HLA‐DR, which is involved in HLA class II‐restricted CD4 + T‐cell immunity, is the major locus that contributes to susceptibility to HB‐ACLF . Therefore, it suggested that the polymorphism of CD4 + T‐cell priming determined the magnitude and quality of CD8 + T‐cell response and hepatic damage.…”
Section: Discussionmentioning
confidence: 91%
“…As reported, CD4 + T‐cell priming is pivotal to activate professional antigen‐presenting cells necessary for the induction of CD8 + T‐cell responses . And a recent genome‐wide association study identified that HLA‐DR, which is involved in HLA class II‐restricted CD4 + T‐cell immunity, is the major locus that contributes to susceptibility to HB‐ACLF . Therefore, it suggested that the polymorphism of CD4 + T‐cell priming determined the magnitude and quality of CD8 + T‐cell response and hepatic damage.…”
Section: Discussionmentioning
confidence: 91%
“…Genetic variations in HLA class II loci (HLA-DP and HLA-DQ) were significantly associated with susceptibility to chronic HBV infection and with HBV-related HCC (Mbarek et al, 2011;Kamatani et al, 2009;Nishida et al, 2012;Jiang et al, 2013;Jiang et al, 2015;Li et al, 2012;Kim et al, 2013;Hu et al, 2013;Chang et al, 2014;Tan et al, 2017) ( Table 1, Fig. 2).…”
Section: Hbv and Hcvmentioning
confidence: 98%
“…Excess innate immune responses to viral antigens mediated by pathogen‐associated molecular patterns and damage‐associated molecular patterns (DAMPs) may play a role in the development of ACLF . Host and virus genetic factors have also been shown to predispose certain individuals to ACLF due to HBV . However, our ability to predict ACLF due to HBV still remains poor.…”
Section: Viral Hepatitismentioning
confidence: 99%